Strategi Komunikasi Efektif Pengelolaan Arsip Digital untuk Mendukung Layanan Inklusif bagi Disabilitas Tuli di PT KAI Tahun 2025 - Hasbi Ridla Ilahi; Agus Taryana; Wawat Setiawati (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
Effective communication is a pivotal component in the provision of inclusive digital archive services, particularly for individuals who are Deaf and depend on visual communication and Indonesian Sign Language (Bisindo). The objective of this study is threefold: first, to analyze the communication process in the management of digital archives at PT Kereta Api Indonesia (Persero); second, to identify communication barriers experienced by Deaf individuals; and third, to formulate strategies for developing inclusive digital archive services. The research employs a descriptive qualitative approach with participatory observation, interviews, and documentation studies at the Section of Asset Ownership Document and Files (USDA) of PT KAI. Participatory observation was conducted to directly observe the steps in using the Rail Document System (RDS), the workflow of digital archive services, and the interactions between Deaf and hearing staff members. Over two months, in-depth data were collected through observation, interviews, and documentation involving seven informants, both internal and external. The results indicate that the management of PT KAI's digital archives has been technically well-executed; however, it does not fully accommodate the needs of Deaf users. The study proposes several recommendations, including the integration of Indonesian Sign Language (Bisindo) into the digital archive system, the provision of content or features accompanied by visual guides, the implementation of sign language training for PT KAI employees, and the reinforcement of internal company policies and regulations. These recommendations aim to ensure the provision of equitable and inclusive digital archive services at PT KAI